1998
DOI: 10.1046/j.1360-0443.1998.93456111.x
|View full text |Cite
|
Sign up to set email alerts
|

Treating alcohol problems: a study of programme effectiveness and cost effectiveness according to length and delivery of treatment

Abstract: A two week in- and day-patient treatment was more cost effective than a 5-week inpatient treatment. Design limitations make these conclusions tentative pending a randomized controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 43 publications
2
14
0
1
Order By: Relevance
“…areas compared to 79.8% nationally. 27 Parts of the state are particularly remote. Substance abuse, and especially alcohol abuse, appears to be a serious problem in the state.…”
Section: Quantity Of Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…areas compared to 79.8% nationally. 27 Parts of the state are particularly remote. Substance abuse, and especially alcohol abuse, appears to be a serious problem in the state.…”
Section: Quantity Of Treatmentmentioning
confidence: 99%
“…32 Our analysis focuses on the …fteen largest publicly funded substance abuse agencies, who had a combined budget of $6; 439; 312 in …scal year 1994 of which $4; 594; 595 was budgeted for outpatient treatment alone. 33 Our treatment provider 27 Data are from the census website: http://www.census.gov/statab/www/states/me.txt. 28 Source: Maine's application for the Alcohol, Drug Abuse and Mental Health block grants in FY 1992 29 Source: Maine OSA Fact Sheet, "Alcohol Use in Maine," 1997.…”
Section: Quantity Of Treatmentmentioning
confidence: 99%
“…More recent studies have challenged this belief, citing that outcomes were no different when program length was reduced in inpatient treatment (Long, Williams, & Hollin, 1998), day treatment (Bamford, Booth, McGuire, & Salmon, 2003), and therapeutic community settings (McCusker et al, 1997;McMahon, Kouzekanani, & Malow, 1999). Paradoxically, McCusker et al (1997) found that dropouts assigned to 6-month relapse prevention were likely to relapse sooner than clients assigned to a 3-month program with similar content, even though treatment time overall was greater for the dropouts.…”
Section: Introductionmentioning
confidence: 91%
“…A further three relevant papers studying the cost-effectiveness of different service provision options were identified by the current literature review (Hayashida et al, 1989;Agosti, 1994;Long, Williams, & Hollin, 1998). Hayashida et al (1989) found that 66% of ambulatory detoxified patients became abstinent compared to 81% of the patients with institutionalized detoxification.…”
Section: Clinical and Cost-effectiveness Of Alcohol Dependence Treatmmentioning
confidence: 99%